TADARRUJ FI AT-TASYRI’ KEHARAMAN RIBA DALAM TAFSIR AL-MISBAH DENGAN PENDEKATAN LINGUISTIK - Haqiqi, Muhamad; Ikhsan, Muhammad; Fahruli, Sehilana; Mahfudz, Yusuf Nur; Saputra, Okta (Prodi Ilmu Al-Qur'an dan Tafsir, 2022)
Usury is something that is strictly prohibited in Islam, because usury is considered a form of extortion against the indigent. The expectation of usury in Islamic law, decided gradually, this rule is called the rule of tadarruj fi at tasyri'. Riba in the Koran is discussed in four surahs, among them Ar-Rum verse 39, An-Nisa verse 161, Ali Imran verse 130 and Al-Baqarah verses 275-279. This study aims to find out tadarruj fi at tasyri' and indicate lafadz and its benefits which show the differences between the stages of usury expectations and the interpretation of Al-Misbah as the primary reference source. The method of this study uses a literature method with a linguistic approach that looks at data descriptively and qualitatively. The results of the research obtained are the process of usury expectation along with indications from each verse that discusses tadarruj fi at tasyri' usury forbiding.